Successful Endoscopic Injection Sclerotherapy of High-Risk Gastroesophageal Varices in a Cirrhotic Patient with Hemophilia A - Kohei Fukumoto; Hideyuki Konishi; Koichi Soga; Ki-ichiro Miyawaki; Hitoshi Okano; Masahito Minami; Naoki Wakabayashi; Shoji Mitsufuji; Norimasa Yoshida; Tomohisa Takagi; Nobuaki Yagi; Yuji Naito; et al. (Gastroenterology Research and Practice)
A 68-year-old man with hemophilia A and liver cirrhosis caused by hepatitis C virus was referred to our hospital to receive prophylactic endoscopic treatment for gastroesophageal varices (GOV). He had large, tense, and winding esophageal varices (EV) with cherry red spots extending down to lesser curve, predicting the likelihood of bleeding. Esophageal endoscopic injection sclerotherapy (EIS) was performed with a total 15 mL of 5% ethanolamine oleate with iopamidol (EOI). Radiographic imaging during EIS demonstrated that 5% EOI reached the afferent vein of the varices. He was administered sufficient factor VIII concentrate before and after EIS to prevent massive bleeding from the varices. Seven days after EIS, upper gastrointestinal endoscopy (UGIE) showed that the varices were eradicated almost completely. Eighteen months after EIS, the varices continued to diminish. We report a successful case of safe and effective EIS for GOV in a high-risk cirrhotic patient with hemophilia A.